Quality seed production and seed cane economy for better resource use efficiency - Kumar, Navnit; Rana, Lalita; Kumar, Anil; Singh, S N; Singh, A K (Indian Farming, 2022)
Seed is the most significant basic input and is alone responsible for improving crop productivity by 15–20%, ensuring the production and supply of high-quality seed is the key to agricultural production stability. Higher cane and sugar productivity per unit area is mostly dependent on steady supplies of high-quality seed canes that are genetically pure, pest and disease-free and nutritionally sound. A new variety takes 8–10 years to establish itself in a farmer’s field using the traditional form of seed multiplication (3 budded setts), which has a multiplication ratio of 1:10. Some of the seed saving techniques such as bud chip, polybag and tissue culture raised plants are less voluminous and easy to handle with care and are free from pests and diseases. Though propagation through polybags is labour intensive and development of tissue culture plants is tough in farmers’ fields. Bud chip technology allows for saving a lot of seed (80%) and is also called seed saving technology. Insect pests and diseases can be avoided during bud scooping when sugarcane is cultivated utilizing the bud chip method. Bud chip is a simple, reliable, and farmer-friendly technology for replicating seeds of newly released varieties quickly.